(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2013)
An investigation was carried out to identify the extent of genetic divergence of seventeen vegetable pea genotypes at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh. Genetic divergence was estimated using D2 and principal component analysis. The genotypes under study fell into 4 clusters. The distribution pattern indicated that the maximum numbers of genotypes (6) were included in cluster II and cluster III and the minimum number in cluster IV (1). The inter-cluster distance was higher than the intra-cluster distance which indicated wider genetic diversity among the accessions of different groups. The highest inter-cluster distance was observed between II and IV. The lowest inter-cluster distance was observed between clusters II and III suggesting a close relationship among the genotypes of these two clusters. The highest intra-cluster distance was observed for the cluster II. The positive values of vector I and vector II for plant height, 50% flowering and non-reducing sugar indicated that these characters had the highest contribution towards the divergence among the pea genotypes. The genotypes of vegetable pea from cluster II and cluster IV maybe selected as parents in future hybridization program. DOI: http://dx.doi.org/10.3329/bjpbg.v26i1.19982